Structural modeling, Cloning, Expression and Purification of Toxoplasma gondii dense granule protein 3 (GRA3) in E.coli (2016)
Toxoplasma gondii is an apicomplexan parasite responsible for Toxoplasmosis, a disease with a high prevalence in tropical and subtropical regions and also in Europe. GRAS proteins of Toxoplasma gondii including GRA3, GRA5, GRA7 and GRA8 have significant roles in the host-parasite interaction. They have the capacity to alter and modulate the expression and activity of the host cell; facilitating the invasion and stabilization of parasite within the cells. Specifically, GRA3 protein is important for the virulence phenotype of the type II strains of Toxoplasma gondii. Like many dense granules, GRA3 has no homology to proteins with described structure. A 3D theoretical model of GRA3 was built by an ab initio approach and by searching of structural orthologs we found structural similarity with BCL-XL (PDB id 1Bxl). T. gondii GRA3 has two conserved transmembrane regions like BCL-2 family members and an elongated hydrophobic cleft. This cleft may represent the binding site for other members of the Bcl-2. In the molecular docking between GRA3 model and Bak as a ligand, the binding free energy was -5.2 kcal / mol. This was congruent with the control docking between BCL-XL and Bak with a binding free energy of -5.7 Kcal / mol. Finally, recombinant protein GST-TgGRA3 expressed in E. coli and it was purified by affinity chromatography with GST column in the AKTA system in native conditions. The purification of recombinant GST-TgGRA3 was confirmed by Western-blot.